News and Analysis : LGBT+ scientists consider leaving work due to discrimination. (14th October 2019) - Tesh, Sarah
Abstract: Almost a third of LGBT+ physical scientists in the UK have considered leaving their jobs because of discrimination and toxic workplace climates.